Pandemic (H1N1) 2009 and Hajj Pilgrims Who Received Predeparture Vaccination, Egypt - Amr Kandeel; Michael Deming; Eman Abdel Kereem; Samir El-Refay; Salma Afifi; Mohammed Abukela; Kenneth Earhart; Nasr El-Sayed; Hatem El-Gabaly (Emerging Infectious Diseases, 2011)
In Egypt, vaccination against pandemic (H1N1) 2009 virus was required of pilgrims departing for the 2009 Hajj. A survey of 551 pilgrims as they returned to Egypt found 542 (98.1% [weighted]) reported receiving the vaccine; 6 (1.0% [weighted]) were infected with influenza virus A (H3N2) but none with pandemic (H1N1) 2009 virus.